Early literacy programme as support for immigrant children and as transfer to early numeracy. Issue 3 (3rd April 2017) - Korat, Ofra; Gitait, Aviva; Bergman Deitcher, Deborah; Mevarech, Zmira
ABSTRACT: We researched the efficacy of an early literacy programme in enhancing immigrant children's phonological awareness (PA) and print knowledge, including transferring learning to numeracy. Participants were 294 Ethiopian-born immigrant children in Israel at kindergarten age and one of their parents. Parent–child dyads were randomly selected to receive an intervention computer program focused on PA and print knowledge (letter names, letter–sound connections, and print knowledge) or a control computer program focused on general cognitive abilities (spatial perception, eye–hand coordination) and language skills (e.g. colours). Following the activity, greater improvement was found in PA, print knowledge, and numeracy in the intervention group compared to the control group. The intervention had a unique contribution to children's progress in the three variables, with no contribution for child's background. Furthermore, PA progress in the intervention group contributed significantly to children's numeracy beyond the intervention's contribution. Implications for education and future studies are discussed.